Low Genetic Diversity Study on Leopard Coral Grouper Plectropomus leopardus (Perciformes: Serranidae) from Sulawesi, Indonesia - Andi Aliah Hidayani; Asmi Citra Malina A. R. Tasakka; Widyastuti Umar; Md. Jobaidul Alam; Amit Kumer Neogi; Sapto Andriyono (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research • The leopard coral grouper Plectropomus leopardus was identified and analysed based on molecular approach. • Genetic diversity within two regions in Gorontalo, Sulawesi successfully performed using connectivity analysis. • Three haplotypes of Plectropomus leopardus from two region in Gorontalo as one of economical important marine fish species.